Estudo comparativo entre es as esquadrias de alumínio e as de PVC na construção civi - Albuquerque, Eduardo Saeger Cavalcanti de (2017)
Frames represent one of the most expensive items of a construction, so it is always necessary to carry out comparative studies between materials offered and with new technologies for the application. Given that PVC may be gaining market in the coming years, this study makes a comparison between aluminum and PVC materials. The frames have to obey some items cited in technical standards, such as watertightness, air permeability, wind resistance, durability, thermo-acoustic insulation, among others. From this form, we will show the production processes and technical standards of each of the two materials under study. Finally, a cost comparison was made between the aluminum and PVC frames and the market for this product was analyzed in the city of João Pessoa-PB